ACCEPTANCE AND USE OF ARTIFICIAL INTELLIGENCE (AI) AMONG NURSING STUDENTS: A SCOPING REVIEW - Annisa Pratiwi; Zainal Abidin; Rizeki Dwi Fibriansari; Anggia Astuti (Udayana University, 2025)
Artificial intelligence (AI) had the potential to transform nursing education and practices. Nursing students need to be prepared to understand, accept, and use AI. However, nursing students experienced various challenges in using AI. This scoping review aimed to map the literature related to the acceptance and use of AI among nursing students. This scoping review followed the framework by Arksey and O’Malley. Inclusion criteria were AI-related studies involving nursing students, published in English (2015-2025), and available in full text. The search and selection of articles were shown in the PRISMA-SR flow diagram. Data extraction was done by creating a table. This research identified nine articles. Most studies reported positive attitudes and high readiness among nursing students to accept and use AI. Students used AI for learning, completing academic assignments, and supporting clinical practice. Influencing factors included AI literacy, personality, smart device addiction, and prior technology experience. Main challenges identified were lack of AI-focused training and curriculum, financial barriers, and concerns about data reliability. Nursing students generally demonstrated positive acceptance and use of AI, but significant gaps remained in training, curriculum integration, and access. These challenges are addressed through structured education, financial support, and ethical guidelines to optimize AI in nursing education and practices.